The Basque civil neighbourhood and the intertemporal conflicts in the Basque civil law - Magallon Elósegui, Nerea (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Through the Basque Civil Law Act 5/2015 the Basque civil neighbourhood is created, which implies an automatic change of civil neighbourhood of all those who have a civil neighbourhood in one of the territories of the autonomous Community of the Basque Country. Its creation revives again the discussion on the competition between the CCAA and the State to respond to conflicts arising from interaction between various territorial legislative systems or internal conflicts. At the same time this creation involves the potential multiplication of the problems adhering to the mobile conflict in successions. This paper will first analyze the adequacy of the new civil neighbourhood to the constitutional parameters and, secondly, the problems of intertemporal law that originates, illustrated through the Resolution of the Directorate General of Registries The Notarized, of June 12, 2017, which projects this new reality on the practice.